Can the G20 serve as a launchpad for a multilateral investment agreement? - Axel Berger; Wan-Hsin Liu (The World Economy, 2021)
The international system for the governance of foreign investments is highly fragmented consisting mainly of bilateral agreements. With the adoption of nine guiding principles for global investment policy-making in 2016, some observers argue that the G20 can actually serve as a launchpad for negotiations of a multilateral investment agreement. This paper provides empirical evidence on the question of whether the contents of international investment agreements (IIAs) have gradually converged to facilitate the multilateralisation of investment rules. We find that IIAs negotiated among non-G20 countries are more similar to each other than those concluded by G20 countries in general and even more so since 2000 in particular. This result calls into question the premise that the G20 can serve as the most suitable forum to initiate multilateral negotiations on multilateral investment rules. Instead, an extended analysis using different country grouping criteria suggests that the Member States of the European Union may be a more suitable alternative in this regard. Here, the EU can jointly take a leading role in facilitating related negotiations on multilateral investment rules.
Keywords: 330; EU; G20; investment agreements; OECD; similarity